Dampak Perundungan terhadap Kesehatan Mental Mahasiswa Fakultas Kedokteran - Tatambihe, Brainly M. H.; Dundu, Anita E.; Kairupan, Bernabas H. R. (Universitas Sam Ratulangi, 2026)
Abstract: Bullying behavior often occurs in learning environments, including medical education with seniors as executor in most cases. Not everyone has the psychological defense to deal with bullying. Therefore, bullying can cause impacts that not only affect the victims’ psychology but also their performance in the future. This study aimed to obtain bullying behavior among medical students and its impacts on the medical students. This was a systematic review study using databases of Google Scholar, Pubmed, and Clincal Key. The literatures used to be in Indonesian or English, published in last five years. The results obtained nine articles from several countries. Bullying still occurred in medical environments. Moreover, bullying could cause depression, anxiety, and other mental disorders to their victims. The lack of reported cases supported the large number of cases of bullying in the medical environment. In conclusion, bullying is still common in medical environment, and causes decreased academic prestation and many mental disorders. Keywords: bullying; mental impacts; medical students Abstrak: Perilaku perundungan sering terjadi di lingkungan pembelajaran, termasuk pembelajaran kedokteran dengan para senior sebagai pelaku di kebanyakan kasus. Tidak semua individu memiliki pertahanan psikologis untuk menghadapi perundungan. Perundungan menyebabkan dampak yang tidak hanya berdampak bagi psikologis korban tetapi juga bagi kinerja korban di masa depan. Penelitian ini bertujuan untuk mengevaluasi perundungan di kalangan mahasiswa kedokteran serta dampaknya bagi korban perundungan. Jenis penelitian ialah systematic literature review dengan menggunakan database Google Scholar, Pubmed, dan Clinical Key. Literatur yang digunakan menggunakan bahasa Indonesia dan bahasa Inggris, yang diterbitkan dalam lima tahun terakhir. Hasil penelitian mendapatkan sembilan artikel dari berbagai negara. Perundungan masih sering terjadi di lingkungan kedokteran. Perundungan menyebabkan depresi, kecemasan, dan gangguan mental bagi para korban. Kurangnya tingkat pelaporan mendukung tingginya angka perundungan di lingkungan kedokteran. Simpulan penelitian ini ialah perundungan di lingkungan kedokteran masih banyak ditemukan dan menyebabkan penurunan prestasi akademik dan berbagai gangguan mental. Kata kunci: perundungan; dampak mental; mahasiswa kedokteran